Yeast programed cell death and aging - Côrte-Real, Manuela (2013)
[Excerpt] Similarly to metazoans, yeast cells can exhibit several characteristics of apoptosis, including chromatin condensation, DNA breakage, flipping of phosphatidylserine to the outer leaflet of the plasma membrane, accumulation of reactive oxygen species (ROS), and release of pro-death factors such as cytochrome c or Endonuclease G from mitochondria. Yeast programed cell death has been shown to occur in response to a variety of stimuli, such as oxidative stress, exposure to acetic acid, and expression of mammalian pro-apoptotic proteins. This program is also inherent to the yeast life cycle, as aged mother cells and cells exposed to pheromone also display an apoptotic and necrotic phenotype. Yeast therefore comprises a conserved core programed cell death process that shares several regulators with mammalian cells, which play major roles in the pathogenesis of human diseases. At the same time, it lacks many of the cell death regulators that have evolved in higher eukaryotes, probably due to the invention of multicellularity. The simplicity of the yeast model allows elucidating the basic molecular pathways of programed cell death without interference from multifaceted regulation, due to various protein isoforms or cellular specificity often observed in studies using mammalian systems. In addition, yeast heterologous expression systems offer the opportunity to exploit the individual functional and mechanistic properties of mammalian apoptotic regulators. [...]